The relation of airway obstruction to asthma, chronic rhinosinusitis and age: results from a population survey of adults. Issue 9 (19th July 2014) - Obaseki, D.; Potts, J.; Joos, G.; Baelum, J.; Haahtela, T.; Ahlström, M.; Matricardi, P.; Kramer, U.; Gjomarkaj, M.; Fokkens, W.; Makowska, J.; Todo‐Bom, A.; et al.
Abstract Rationale There is conflicting evidence on whether patients with asthma experience an accelerated decline in lung function with age. We examined the association between postbronchodilator lung function, asthma, chronic rhinosinusitis (CRS), and atopy with age using a large European sample. Methods In 17 centers in 11 European countries, case–control studies were nested within representative cross‐sectional surveys of adults aged less than 75 years. Representative samples of participants with asthma, CRS or both and controls were assessed for postbronchodilator ventilatory function, smoking history, atopy, and treatment. Multiple regression was used to assess the interactive effects of age and diagnostic group on decline in postbronchodilator ventilatory function. Results A total of 3337 participants provided adequate data (778 with asthma, 399 with CRS, 244 with both asthma and CRS and 1916 controls who had neither asthma nor CRS). Participants with asthma had lower FEV1/FVC (−4.09% (95% CI: −5.02, −3.15, P < 0.001) and a steeper slope of FEV1/FVC against age (−0.14%/annum [95%CI: −0.19, −0.08]) equivalent to smoking 1–2 packs of cigarettes per day. Those with atopy had a slope equivalent to controls. Conclusions People with asthma have a steeper decline in postbronchodilator lung function with age, but neither CRS nor atopy alone were associated with such decline.